Shalat Jama’ Mempelai Wanita Menurut Hukum Islam (Studi Kasus di Desa Kuranji, Kecamatan Kuranji Kota Padang) - Amri Effendi (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2022)
The focus of the study in this article is the law of jamming prayers for the bride at the wedding. Jama' prayers are basically permitted by Islamic teachings, to provide convenience if there are obstacles that are syar'i in nature, but what about the case with a wedding party, is it a syar'i obstacle, and what is the view of Islamic law towards the bride and groom who jama' prayers on the day of the party? marriage. In discussing this issue, the authors use qualitative methods using a